PROFIL PENDERITA FAKOEMULSIFIKASI KATARAK SENILIS DI RSUD SIMPANG LIMA GUMUL KEDIRI PERIODE JULI SAMPAI DESEMBER 2022 - Wahyu Afif Mufida; Noor Areza Adhi Pratama; Dini Dharmawidiarini (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Introduction: Cataract is defined as the opacity of the lens that causes a progressive decrease in visual acuity. Cataract is the leading cause of blindness worldwide. East Java has the highest prevalence of blindness in Indonesia, with cataracts being the main cause. Purpose: To determine the characteristics of senile cataract phacoemulsification patients at Simpang Lima Gumul General Hospital, Kediri, from July 2022 to December 2022. Methods: This study used a descriptive retrospective method with a total sampling of medical record data. There were 89 medical records that met the criteria, and then the frequency distribution for each variable was calculated. Results: Of the 89 patients, 38 (42.7%) males and 51 (57.3%) females had phacoemulsification procedures, the majority were 60–69 years old 48 patients (48.3%). Most of them came with senile cataract grade 3 in 35 patients (39,3%), which occurred bilaterally in 48 patients (53.9%). The highest education level was Elementary School 54 patients (60.7%) and farmers 30 people (33.7%). 45 patients (50.6%) had a history of comorbidities such as hypertension 35 people (39.3%), diabetes mellitus 21 people (23.6%), history of other eye diseases 3 people (3.4%), and other diseases 15 people (16.9%). Uncorrected visual acuity <3/60 in 52 people (58.4%). Conclusion: Most of the characteristics obtained included senile cataract grade 3, bilaterally, female, highest education was Elementary School, farmer, having comorbidities, and coming with blindness.